(3GdeYdbGJ GdYTQs - (3GeQD GdbjS Hf MLQ Hf GdMGQK GdcfOj, ef Hfj Bcd GdeQGQ , J (B80 (3b g`s
(3ChdgG (B:s
(3bGd GeQD GdbjS Hf MLQ Hf GdMGQK GdcfOi baG fHc ef PcQi MHjH hfRd HSbW Gddhi Hjf GdONhd aMhed s
(3BNQgG (B:s
(3hcCfeG GdJbJJ HLjO LPGHI QTGA ef GdZRdGf MQGR be fHjJ YeQkG ZjQ TGcQ fYeJi hGdcaQ eNHKI dfaS GdefYe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B351s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(2/1507) s
Keywords: (3GdCOHs